Neighborhood Signaling Effects, Commuting Time, and Employment: Evidence from a Field Experiment - Magnus Carlsson; Abdulaziz Abrar Reshid; Dan-Olof Rooth (Institute of Labor Economics (IZA), 2018)
The question of whether and how living in a deprived neighborhood affects the labor market outcomes of its residents has been a subject of great interest for both policy makers and researchers. Despite this interest, empirical evidence of causal neighborhood effects on labor market outcomes is scant, and causal evidence on the mechanisms involved is even more scant. The mechanism that this study investigates is neighborhood signaling effects. Specifically, we ask whether there is unequal treatment in hiring depending on whether a job applicant signals living in a bad (deprived) neighborhood or in a good (affluent) neighborhood. To this end, we conducted a field experiment where fictitious job applications were sent to employers with an advertised vacancy. Each job application was randomly assigned a residential address in either a bad or a good neighborhood. The measured outcome is the fraction of invitations for a job interview (the callback rate). We find no evidence of general neighborhood signaling effects. However, job applicants with a foreign background have callback rates that are 42 percent lower if they signal living in a bad neighborhood rather than in a good neighborhood. In addition, we find that applicants with commuting times longer than 90 minutes have lower callback rates, and this is unrelated to the neighborhood signaling effect. Apparently, employers view information about residential addresses as important for employment decisions.
Keywords: C93; J15; J21; J71; 330; neighborhood signaling effects; neighborhood stigma; commuting time; discrimination; field experiment; correspondence study